Implementasi PSAK 65 pada Laporan Keuangan Konsolidasi PT Astra Agro Lestari Tbk dan Entitas Anak - Putri Aosiliana; Arlitha Putri Anggraeni; Sherindea Permata Agita (Universitas Katolik Widya Karya Malang, 2024)
Companies face the challenge of achieving goals and objectives with effective, efficient and risk-free operations. One strategy that is commonly used is opening new branches or establishing new branches. This research focuses on PT Astra Agro Lestari Tbk, an oil palm plantation company, and investigates the implementation of PSAK 65 in preparing consolidated financial statements. PSAK 65 is important for recording transactions during the consolidation process, recognizing subsidiary profits, and preparing financial reports according to general accounting standards. This study involves comparisons with previous research, such as the implementation of PSAK 65 by PT Telkom Indonesia Tbk. This research aims to provide further understanding of PT Astra Agro Lestari Tbk's consolidated accounting practices and compliance with these standards.